PENINGKATAN KETERAMPILAN MENULIS POSTER DENGAN PENDEKATAN KONTEKSTUAL MENGGUNAKANN MEDIA SCRAPBOOK BERTEMA KONSERVASI BUDAYA PADA SISWA KELAS VIII SMP NEGERI 2 RAMBAH - Nurlela Nurlela (JURNAL PENDIDIKAN ROKANIA, 2019)
The purpose of this study is to describe the improvement of poster writing skills, describe the learning process of poster writing skills in progress, and describe the changes in behavior of VIII grade students of SMP Negeri 2 Rambah after getting poster writing learning with a contextual approach using scrapbook media with the theme of language and culture conservation. The method used in this research is classroom action research. The results obtained indicate that the writing skills of eighth grade students of SMPN 2 Rambah increased. The pre-action test results showed an average value of 66.8 and in the first cycle obtained an average value of 70.46. This means an increase of 3.66 points or 5.48%. In cycle II, the class average is 76.43. This shows an increase from cycle I to cycle II of 5.97 points or 8.47%. So the increase that occurred from the pre-action until the second cycle was 9.63 points or 13.95%. Thus, the contextual approach and the use of sticky media on the theme of language and culture conservation can improve the ability to write posters.